Maintenance engineering and management : a guide for designers, maintainers, building owners and operators, and facilities managers CIBSE guide M - Harris, Jo, 1972- (The Chartered Institution of Building Services Engineers, 2014)
This document is intended to bring maintenance into a sharper focus by helping building and property operators become more aware of their responsibilities and duties. It will also help services designers to appreciate their role in providing installations that are safe, economic to maintain and operate, and capable of giving satisfactory performance over their full lifespan. During the process of updating this Guide the Task Group collaborated with other publishers of best practice guidance including RICS, B&ES and BSRIA Ltd to agree a structure for presenting assets. This has resulted in the economic life data provided in Chapter 12 being structured by system and elements, being numbered to match NRM3 and providing maintenance task references to SFG20. CIBSE's Guide M is essential reading for everyone involved in designing, installing or operating building services. It is a comprehensive guide to good practice in the operation and maintenance of buildings.
Keywords: Buildings -- Maintenance -- Great Britain.; Building management -- Great Britain.; elektronické knihy; electronic books